Presidential Decree-Law No. 29 of the Year 2015 On Increasing The Pensions as of 1/7/2015 = قرار رئيس جمهورية مصر العربية بالقانون رقم 29 لسنة 2015 بزيادة المعاشات اعتباراً من 1/7/2015 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic